2020
DOI: 10.1016/j.jinf.2020.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MucorGenius® mucorales PCR assay for the diagnosis of pulmonary mucormycosis

Abstract: Objectives: We aimed to assess the clinical relevance of the marketed pan-mucorales real-time PCR assay MucorGenius® (Pathonostics) on pulmonary specimens relative to that of in-house PCR assays and conventional mycology for the diagnosis of mucormycosis. Methods: In total, 319 pulmonary samples from severely immunosuppressed patients at risk for invasive mold disease (IMD) were retrospectively included. Direct examination, mycological culture, and PCR testing were performed using three genus-specific in-house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…Recent studies have confirmed the value of qPCR in BAL, with regard to earlier diagnosis and better outcomes in cases of pulmonary mucormycosis [102][103][104][105][106][107][108][109][110][111][112][113].…”
Section: Applied and Emerging Molecular Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Recent studies have confirmed the value of qPCR in BAL, with regard to earlier diagnosis and better outcomes in cases of pulmonary mucormycosis [102][103][104][105][106][107][108][109][110][111][112][113].…”
Section: Applied and Emerging Molecular Methodsmentioning
confidence: 87%
“…and Cunninghamella spp. [111]. The commercial assay was user friendly and all qPCR assays used in the study were superior to conventional methods to detect fungal DNA.…”
Section: Applied and Emerging Molecular Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our study, a low yield of BAL fluid cytology and culture in identifying Aspergillus and Mucorales has been reported previously 11,12 . The advent of pan‐fungal and species‐specific nucleic acid amplification methods from the BAL fluid is likely to improve the diagnostic yield in identifying moluds 13–16 …”
Section: Discussionmentioning
confidence: 99%
“…PCR combined with high-resolution melt analysis (PCR/HRMA) has also been described, and showed a sensitivity and specificity of 100% and 93% in one study of 99 BAL samples (9 of which were positive) [122]. MucorGenius (Pathonostics, Maastricht, The Netherlands), is a non-FDA approved semi-quantitative PCR assay that targets 28S rRNA in BAL and biopsy samples and can be run in parallel with AsperGenius, with a TAT of 3 h [140,123].…”
Section: Mucorales-specific Pcrmentioning
confidence: 99%